Expectancy-effects without expectancies: illusory correlations based on cue-overlap - Plessner, Henning; Freytag, Peter; Fiedler, Klaus (European journal of social psychology, 2000)
Expectancy-based illusory correlations have been observed in numerous experiments. Simulations using the connectionist computer model BIAS (Fiedler, 1996) show that such illusory correlations may not always reflect expectancy biases but influences of similarity via cue-overlap. Cue-overlap means that some of the probabilistic cues that indicate the presence of one variable are also indicative of another variable. In an experiment, participants learned two novel concepts pertaining to a fictitious painter and a fictitious artistic style in separate runs. Both concepts were defined by multiple probabilistic cues observable in paintings. For half the participants, the cue systems underlying the perception of the two concepts overlapped, whereas for the other half they did not. In addition, we manipulated whether or not participants expected a positive contingency between artist and artistic style. In the second part of the experiment, a series of paintings was presented that constituted an objective zero correlation between artist and artistic style. Participants' subsequent contingency judgments were assessed by direct and indirect measures. Data analyses revealed main effects for expectancy induction and cue-overlap but no interaction on the direct measure and nearly identical results on the indirect measure. Thus, cue-overlap and expectancy induction independently triggered the development of illusory correlations. Copyright © 2000 John Wiley & Sons, Ltd.